A new species of Volvariella and the first record of Volvariella pulla (Agaricales: incertae sedis) from Thailand - Niego, Allen Grace T.; Sysouphanthong, Phongeun; Thongklang, Naritsada; Hyde, Kevin D.; Phonemany, Monthien; Phookamsak, Rungtiwa; Raspé, Olivier (Phytotaxa, 2021)
A new species and a first record of Volvariella are reported from Thailand based on morphological and phylogenetic evidence. The most important features that distinguish Volvariella rostricystidiata sp. nov. are the broadly clavate to obovoid cheilocystidia with a rostrate apex and the scattered, slender and usually fusiform pleurocystidia, which lack a rostrum. Volvariella pulla, recently described from Vietnam, is reported here from northern Thailand based on morphology and sequence data. Combined ITS and nrLSU gene regions were analyzed to confirm the placement and infer the phylogenetic affinities of the two studied species.